Antibacterial and anti-staphylococcal enterotoxin activities of phenolic compounds - Albano, Mariana [UNESP]; Bergamo Alves, Fernanda Cristina [UNESP]; Murbach Teles Andrade, Bruna Fernanda [UNESP]; Barbosa, Lidiane Nunes [UNESP]; Marques Pereira, Ana Flavia [UNESP]; Ribeiro de Souza da Cunha, Maria de Lourdes [UNESP]; Mores Rall, Vera Lucia [UNESP]; Fernandes Junior, Ary [UNESP] (Elsevier B.V., 2016)
Food safety has been an established research field for many decades. This report describes the antibacterial and anti-staphylococcal enterotoxin properties of major phenolic compounds found in essential oils (cinnamaldehyde, citronellol, eugenol, geraniol and terpineol). The determination of minimum inhibitory concentrations (MIC) against Gram-negative and Gram-positive strains, including methicillin-resistant Staphylococcus aureus (MRSA) and enterotoxin-producing S. aureus (enterotoxins A, B, C and D) were evaluated. Cinnamaldehyde displayed MIC values ranging from 100 to 400 mu g/mL against Gram- positive and Gram-negative bacteria, while the other four compounds showed similar values only against Gram-negative bacteria. For Gram-positive strains, MIC values ranged from approximately 800-1750 mu g/mL Interactions between the compounds and antibacterial drugs were evaluated by disc diffusion and time-kill curve assays against MRSA. Combinations of phenolic compounds that included gentamicin showed the greatest synergistic effect. In vitro treatments with subinhibitory concentrations of phenolic compounds resulted in a decreased production of enterotoxins B and C (SEB and SEC). Transmission electron microscopy was performed to evaluate mechanisms of action for cinnamaldehyde and geraniol against E. coli and MRSA. Cells treated with compounds showed complete loss of membrane integrity, separation of the cytoplasmic membrane from the cell wall, cytoplasmic content leakage and cytoplasmic polarization. Thereby, this work showed in vitro potential of using combinations of phenolic compounds and antimicrobial drugs against S. aureus and the virulence of S. aureus enterotoxin producers. Industrial relevance: Antimicrobial compounds derived from plants are a focus of renewed interest as potential substitutes for artificial food preservatives. In our study subinhibitory concentrations of phenolic compounds had a significant effect on the quantity of enterotoxins produced by Staphylococcus aureus and inhibited the growth of Escherichia coli, Salmonella Enteritidis and other bacteria in microbiological media. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Phenolic compounds; Essential oil; Staphylococcus aureus; Synergism; Staphylococcal enterotoxins